Supportive-educative nursing on knowledge, self-efficacy and medication compliance in pulmonary TB patients - Muhtar, Muhtar; Aniharyati, Aniharyati; Kurniadi, Kurniadi; Kushariyadi, Kushariyadi (International Journal of Public Health Science (IJPHS), 2025)
Tuberculosis (TB) cases are very developed in Indonesia and are ranked second largest in the world with 8.5% of global cases. We aim to analyze the effect of supportive-educational nursing interventions on self-efficacy, medication adherence, and knowledge of TB patients. The research design used is a quasi-experimental with a control group design. The treatment group was given supportive educational nursing using pocketbooks and teaching aids, while the control group was given education by health workers using leaflets. This research was conducted in the Bima city area by randomly selecting pulmonary TB sufferers in seven community health centers. The sample size is calculated use the Slovin formula and get the sample size was 64 people. Wilcoxon sign rank test and Mann-Whitney were used in this research. The findings show that there were differences in knowledge, self-efficacy, and treatment adherence in the intervention group regarding pulmonary TB with p-values=0.000, 0.000, 0.001 respectively. Findings show that in the control and treatment post-test groups, there were differences in the variables of self-efficacy, treatment compliance, and knowledge with p-values=0.001, 0.000, and 0.000, respectively. The conclusion was the intervention given to the treatment group had an impact on increasing self-efficacy, pathophysiology, and knowledge compared to the control group in TB patients.